(2m+3n)+(5n-7m)-(3m+9n)=

Simple and best practice solution for (2m+3n)+(5n-7m)-(3m+9n)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2m+3n)+(5n-7m)-(3m+9n)= equation:


Simplifying
(2m + 3n) + (5n + -7m) + -1(3m + 9n) = 0

Remove parenthesis around (2m + 3n)
2m + 3n + (5n + -7m) + -1(3m + 9n) = 0

Reorder the terms:
2m + 3n + (-7m + 5n) + -1(3m + 9n) = 0

Remove parenthesis around (-7m + 5n)
2m + 3n + -7m + 5n + -1(3m + 9n) = 0
2m + 3n + -7m + 5n + (3m * -1 + 9n * -1) = 0
2m + 3n + -7m + 5n + (-3m + -9n) = 0

Reorder the terms:
2m + -7m + -3m + 3n + 5n + -9n = 0

Combine like terms: 2m + -7m = -5m
-5m + -3m + 3n + 5n + -9n = 0

Combine like terms: -5m + -3m = -8m
-8m + 3n + 5n + -9n = 0

Combine like terms: 3n + 5n = 8n
-8m + 8n + -9n = 0

Combine like terms: 8n + -9n = -1n
-8m + -1n = 0

Solving
-8m + -1n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add 'n' to each side of the equation.
-8m + -1n + n = 0 + n

Combine like terms: -1n + n = 0
-8m + 0 = 0 + n
-8m = 0 + n
Remove the zero:
-8m = n

Divide each side by '-8'.
m = -0.125n

Simplifying
m = -0.125n

See similar equations:

| 0=10+-9y | | (x)*(3)*(6)=64-10 | | (x)x(3)x(6)=64-10 | | -27=y--309/-28 | | 4x+2x+3=52-x | | 3(X+6)-11=100 | | 5x^2*3x^2=y | | 3-9y=10 | | 5/8-1/10= | | 5x^4+x^3-2x^2+2x-65=0 | | 15y+y+20= | | 3/4=1/2+f | | 315=x^3+3x^2-x-3 | | 0.3t+0.7(t-0.5)=4.51 | | x-9(0)=10 | | 0-9y=10 | | 7/3-2x= | | 0.0399x^2+x-75=0 | | (-3-7k)-2= | | (3+5x)(-2+7x)= | | 5x+23x=-24 | | 5x-24=13-9 | | 6(n-4)=24 | | 2cis^2x-3sinx+3=0 | | -3(z-1/5)=-4z | | -3(x+1)=13-x | | 7n-6(8n-7)=5-4n | | -6k(7k+11)= | | g(x)=1/2x-3 | | -10(x+3)+5(3x-5)=4(x-6)+13 | | x(2x+7)=-5 | | s^2+27s+34=0 |

Equations solver categories